The Abscisic Acid Levels of Wheat (Triticum aestivum L. cv. Cakmak 79) Seeds that were Germinated under Heavy Metal (Hg++, Cd++, Cu ++) Stress - Munzuroglu, Omer; Zengin, Fikriye Kirbag; Yahyagil, Zubeyde (Gazi Univ, 2008)
The purpose of this study was to investigate the level of endogenous abscisic acid of wheat seeds germinated in the presence of 60, 90 and 120 ppm of mercury, cadmium and copper salt solutions for 16 hours in order to see their effects on the germination. The levels of abscisic acid were analysed by High Performance Liquid Chromatography (HPLC). The results indicated that abscisic acid levels were affected by the kind and level of heavy metals used in the experiments. The effects of these toxic ions on abscisic acid content were found to be highest for mercury and lowest for copper. Regarding the correlation between the concentrations of the toxic elements, applied changes in endogenous abscisic acid levels in the seeds and germination development indicated that inhibition of germination was related with abscisic acid accumulation in the seeds.
Keywords: Abscisic acid; heavy metal; wheat seeds; germination